2012
DOI: 10.1080/09712119.2012.672309
|View full text |Cite
|
Sign up to set email alerts
|

Histological and micrometric effects of diazinon exposure on adrenal medulla and cortex in mice

Abstract: Histopathological effects of Diazinon (DZ) were studied on adrenal gland in virgin young female mice divided into five groups (10 animals each): (1) Control (untreated); (2) and (3) 9 and 18 mg kg(1 single exposure groups (given distilled water on day 1 and 2 and DZ on day 3); (4) and (5) 9 and 18 mg kg(1 multiple exposure groups (given respective DZ doses on days 1Á3). All doses were applied by gavage. Animals were euthanized by cervical dislocation on day 6. Adrenals were removed surgically for histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Previously, epidemiological studies established correlations between OPs and endocrine system diseases [8,9,10] or infertility [11,12] based on urinary measurements of DEP. The endocrine-disrupting effects of OPs, including chlorpyrifos [13,14,15,16,17,18], diazinon [19,20], malathion [21], triazophos [22], and dimethoate [23], have only been proven in animal studies, which reported a disorder of hormones involved in the hypothalamic‒pituitary‒adrenal [20], hypothalamic‒pituitary‒thyroid [14,17,18,19], and hypothalamic‒pituitary‒gonadal axes [14,15,16,17,21,22,23]. All of these OPs metabolize to DEP in vivo; however, we do not know whether these effects are induced by the parent OPs or the metabolites, especially the non-specific metabolite, DEP.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, epidemiological studies established correlations between OPs and endocrine system diseases [8,9,10] or infertility [11,12] based on urinary measurements of DEP. The endocrine-disrupting effects of OPs, including chlorpyrifos [13,14,15,16,17,18], diazinon [19,20], malathion [21], triazophos [22], and dimethoate [23], have only been proven in animal studies, which reported a disorder of hormones involved in the hypothalamic‒pituitary‒adrenal [20], hypothalamic‒pituitary‒thyroid [14,17,18,19], and hypothalamic‒pituitary‒gonadal axes [14,15,16,17,21,22,23]. All of these OPs metabolize to DEP in vivo; however, we do not know whether these effects are induced by the parent OPs or the metabolites, especially the non-specific metabolite, DEP.…”
Section: Introductionmentioning
confidence: 99%
“…After OPs exposure, studies have shown injury of the adrenal gland parenchyma, both in the cortical and medullar areas, showing that adrenal glands are highly vulnerable at OP exposure, with extensive cytoplasmic lesions and hypertrophy of the fascicular zone as opposed to the reticular area. Migration of medullar cells in the cortical area and a widespread cellular atrophy was also observed in laboratory studied animals [ 15 , 36 ]. We observed a diffuse vacuolization of the cortical area in the adrenal glands.…”
Section: ⧉ Discussionmentioning
confidence: 99%
“…A key stress-responsive organ, the adrenal gland is a component of both the HPA axis and the sympatho-adrenomedullary system (10). The adrenal glands are considered to be among the most important endocrine glands and are involved in many biological functions, including developmental, immune, inflammatory, osmoregulatory, and metabolic activities (11). The adrenal cortex produces several steroid hormones The three outer layers of the endocrine gland-the zona glomerulosa (ZG), the zona fasciculata (ZF), and the zona reticularis (ZR)-as well as the inner medulla make up this structure.…”
Section: Introductionmentioning
confidence: 99%
“…Polydipsia, polyphagia, and polyuria, which are DM symptoms, have been linked to the adrenal gland (12). All of the body's major organs, including the heart, kidney, bones, muscles, and nervous system, are directly impacted by adrenal hormones, including the metabolic metabolism of carbohydrates, proteins, and lipids (11).…”
Section: Introductionmentioning
confidence: 99%